Activation of a small ephemeral lake in southern Jordan during the last full glacial period and its paleoclimatic implications. Issue 1 (21st June 2017) - Catlett, Gentry A.; Rech, Jason A.; Pigati, Jeffrey S.; Al Kuisi, Mustafa; Li, Shanying; Honke, Jeffrey S.
Abstract: Playas, or ephemeral lakes, are one of the most common depositional environments in arid and semiarid lands worldwide. Playa deposits, however, have mostly been avoided as paleoclimatic archives because they typically contain exceptionally low concentrations of organic material, making 14 C dating difficult. Here, we describe a technique for concentrating organic matter in sediments for radiocarbon dating and apply it to playa sediments recovered from a 2.35 m sediment core from a small playa in southern Jordan. Based on 14 C ages of the organic concentrate fraction, the playa was active from ~29 to 21 ka, coincident with the last major high stand of Paleolake Lisan and wet conditions recorded by other paleoclimatic proxies in the southernmost Levant during the last full glacial period (35–20 ka). The timing and spatial pattern of these records suggests that the increased moisture was likely derived from more frequent and deeper eastern Mediterranean (EM) cyclones associated with the intensification of the westerlies. The presence of full glacial pluvial deposits in southern Jordan (29°N), and the lack of similarly aged deposits in the northern Arabian Peninsula to the south, suggests that the southerly limit of the incursion of EM cyclones during last full glacial period was ~28°N.